Resource sharing activities among fisheries libraries under the Ministry of Agriculture in Indonesia a survey with implications towards the development of the Indonesian Fisheries Information System - Sri Wardiningsih R. (Institute of Library Science, University of the Philippines Diliman, 1988)
This study attempts to survey the status and prospects of existing resource sharing activities among thirteen fisheries libraries under the Ministry of Agriculture in Indonesia, and to recommend ways to improve them to further develop the INFIS network.